2016
DOI: 10.1038/ejcn.2016.213
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators as predictors of total body fat and cardiometabolic risk factors in Chilean children at 4, 7 and 10 years of age

Abstract: Relationship between anthropometrical indicators of adiposity and cardiometabolic markers becomes stronger from 7 years onwards; BAZ, WC and WHtR perform similarly as markers of cardiometabolic risk at least until 10 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
10
0
8
Order By: Relevance
“…Among the strengths of our study, we con rm that a risk score composed of metabolic risk factors can be used to investigate the cardiorespiratory tness and muscle strength [16,18,30,45]. Such variables indicators may better re ect the health status of participants than the assessment of individual risk factors [ 59 ].…”
Section: Discussionmentioning
confidence: 90%
“…Among the strengths of our study, we con rm that a risk score composed of metabolic risk factors can be used to investigate the cardiorespiratory tness and muscle strength [16,18,30,45]. Such variables indicators may better re ect the health status of participants than the assessment of individual risk factors [ 59 ].…”
Section: Discussionmentioning
confidence: 90%
“…(2016) describieron valores significativamente superiores en niñas en el porcentaje de masa grasa en comparación a los niños (24,3% y 16%, respectivamente) y valores similares y sin diferencias significativas en la presión arterial (21). Un reciente estudio (22) encontró que los indicadores antropométricos de adiposidad no se relacionaron con los factores de riesgo cardiometabólico a los cuatro años; sin embargo, desde los siete y diez años las asociaciones se volvieron más fuertes y positivas. El aumento de la prevalencia de hipertensión arterial en niños y adolescentes se ha convertido en un importante problema de salud pública y ha conducido a una cantidad considerable de investigaciones que buscan mejorar su diagnóstico y tratamiento (23).…”
Section: Discussionunclassified
“…According to a study by Vasqez et al (2017), anthropometric adiposity indicators become associated to cardiometabolic markers only from the age of 7 years, with associations being slightly higher at 10 years [24]. At all ages the BMI to age, the WC and the waist-to-height ratio correlate with cardiometabolic markers, therefore they are more sensitive in determining cardiometabolic risks, while the WHR is a slightly weaker marker [24].…”
Section: Discussionmentioning
confidence: 99%
“…At all ages the BMI to age, the WC and the waist-to-height ratio correlate with cardiometabolic markers, therefore they are more sensitive in determining cardiometabolic risks, while the WHR is a slightly weaker marker [24]. A study by Qi et al (2017) in 8 to 16-year-olds found that in boys, the BMI, the WC and the percentage of BF showed the strongest association with insulin resistance, and was signifi cantly stronger compared with the fat mass index than the WHR; in girls, the percentage of BF showed a signifi cantly stronger association with insulin resistance compared with the BMI, the WC, the WHR [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation